Paediatricians’ attitudes and beliefs towards transgender people: a cross-sectional survey in Israel - Nitsan Landau; Uri Hamiel; Itay Tokatly Latzer; Elinor Mauda; Noah Levek; Liana Tripto-Shkolnik; Orit Pinhas-Hamiel (BMJ Open)
Objective The number of transgender and gender non-conforming children is on the rise. For these children, the timing of medical intervention is crucial, yet transgender children report poorer overall physical and mental health outcomes compared with their cisgender peers. We aim to describe how paediatricians perceive transgender people.Setting The ‘Transgender Attitudes and Beliefs Scale’, which consists of 29 items in three domains—human value, interpersonal comfort and sex/gender beliefs—was administered to 391 senior and resident paediatricians in Israel. The responses on a 7-point Likert scale were collapsed into two categories: a mean score of ≥6 for each domain was a ‘Favourable’ perception and <6 ‘Unfavourable’.Results Of 355 respondents (91% response rate), 221 (62%) were females, 132 (37%) were males and 2 identified as ‘other’; 290 (82%) were born in ‘trans-respect countries’, 274 (77%) identified as secular, 223 (63%) were senior physicians and 132 (27%) were residents. Overall, 90% of the cohort scored favourably on the ‘Human value’ domain, 68% on ‘Interpersonal comfort’ and 40% on ‘Sex/gender beliefs’. In the ‘Interpersonal comfort’ domain, being a man, birthplace in a transphobic country, identification as religious and being a senior physician were all associated with increased ORs for an unfavourable score: 2.1 (95% CI 1.3 to 3.4), 3.4 (95% CI 1.9 to 6.3), 2.4 (95% CI 1.4 to 4.2) and 1.8 (95% CI 1.1 to 3.0), respectively. In the ‘Sex/gender beliefs’ domain, being a man and identifying as religious had significantly increased ORs for unfavourable scores: 2.2 (95% CI 1.3 to 3.5) and 10.6 (95% CI 4.7 to 24.1), respectively.Conclusions Negative attitudes towards transgender people are still widespread among paediatricians. Interventions are warranted to positively impact these attitudes.